Effect of Aging Time in the Synthesis of Biogenic Hydroxyapatite Derived from Cockle Shell - Siti Hajar, Saharudin; Jun Haslinda, Haji Shariffuddin; Noor Ida Amalina, Ahamad Nordin; Aqeela, Ismail (Elsevier Ltd, 2019)
Cockle shell wastes are abundant, easily available and can be obtained at low cost. It is rich in calcium carbonate (CaCO3) that can be precursor to synthesis hydroxyapatite (HAP). The HAP has potential to be used in numerous applications such as biomedical and wastewater treatment. The overall objective of this study is to determine the effect of aging time on the production of HAP derived from cockle shells waste. There are two aging times used in this study which are 3 and 5 h. The processes involved in synthesizing HAP were pretreatment of the cockle shells, production of CaCO3 in aragonite form, calcination of the CaCO3 to form CaO, production of Ca(OH)2 and finally reaction of the Ca(OH)2 solution with the phosphate source to obtain HAP. All samples have undergone physicochemical analyses to determine their phases, crystallinity, purity, functional group, surface morphology and elemental analysis using X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM) and Electron Dispersive X-ray Analysis (EDX). This study found that 5 h aging time produced higher crystalline HAP compared to the others. Overall, this study proved that aging time play vital role in the quality of the synthesized HAP.